EVALUASI KINERJA REPRODUKSI SAPI FRIESIAN HOLSTEIN IMPOR DI BALAI BESAR PEMBIBITAN TERNAK UNGGUL-HIJAUAN PAKAN TERNAK BATURRADEN - , DWI YANTO, Dr. Ir. Adiarto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted to evaluate the reproductive performance of imported Friesian Holstein in Balai Besar Pembibitan Ternak Unggul-Hijauan Pakan Ternak (BBPTU-HPT) Baturraden. Seventy seven heads of FH which had three cycles of lactation were used in this research. The data of calving interval (CI), post partum mating (PPM), services per conception (S/C), and cycle of oestrus (SE) were collected. Reproduction performance was analyzed by correlation and regression